PENGUJIAN KINERJA WEB SERVER ELASTIC CLOUD COMPUTE (EC2) FREE TIER PADA AMAZON WEB SERVICE (AWS) MENGGUNAKAN JMETER - Nur Hidayat, Andi Muhammad; Rizaldy, Adhy; Hartono, Nahrun; Harwalis, Harwalis (Program Studi Sistem Informasi, Universitas Banten Jaya, 2024)
The research aims to evaluate the capacity of Amazon Web Service's (AWS) Elastic Cloud Compute (EC2) Free Tier Web Server using the JMeter testing tool. The objective is to ascertain the extent of the server's load-bearing capabilities. Tests were conducted, loading 500 users within a 10-second range and 1000 users within a 1-second range. Despite being a free service, test results showed the server's capability to handle high loads without errors (0% error rate). These findings illustrate the free service's ability to maintain stable performance under significant user loads. The utilization of EC2 Free Tier on AWS demonstrates its capacity to handle heavy tasks without compromising service quality. From about 5 steps in each of two tests, the value for sample time / response time in the initial test of the Amazon Web Service Web server is 59 / ms (millisecond) and the average latency value in the second test, namely 7.213 /ms (millisecond). Both of these gained CPU Utilization from minum, average and maximum with final rate are zero Error. This outcome concludes that the free server possesses robust and reliable capabilities, instilling confidence in an effective and efficient server solution even under high usage levels without additional costs.